Pembuktian Konsep Law Of One Price (LOOP) Dalam Absolute Purchasing Power Parity Menggunakan The Big Mac Index Antar Negara The Six Cheapest (Indonesia – Malaysia) Per Juli 2021 - Pangestuti, Dewi Cahyani; Riantiarno, R. Ferry (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to prove the existence of the absolute purchasing power parity theory using The Big Mac Index and take the example of The Six Cheapest countries, two of which are Indonesia and Malaysia. The data taken is secondary data that has been measured and processed by The Economist which contains the prices of the Big Mac units sold by each country, in The Big Mac Index is 56 countries with different incomes. The method used is a descriptive method, with the literature method technique. The results show that in the end absolute purchasing power parity will not be formed in the free market. This is stated by the non-meeting points of purchasing power parity under conditions of real consumption. Also, it is proven by the undervalued value of the rupiah and ringgit in Indonesia and Malaysia against the US dollar, as well as the level of consumption of each country that must be adjusted.